Navigating unique challenges: librarian perceptions in supporting physician associate (assistant) programs. - Jaskowiak, Megan; Ott, Michelle Nielsen; Kletscher, Karina (Journal of the Medical Library Association, 2026)
Objectives: This study examines the experiences of librarians who support physician assistant/associate (PA) programs, describing the unique challenges of these programs and outlining strategies that librarians adopt to engage these programs. Method: This mixed-methods study includes two phases: (1) a quantitative survey developed and distributed to library personnel in institutions with established or developing PA programs in the US and Canada, and (2) semi-structured interviews with fifteen selected survey respondents, focusing on their experiences and perceptions related to PA education support. The qualitative data were analyzed using thematic analysis. Results: Seventy-five survey responses were collected. Key findings from the survey include: most respondents were from universities with health sciences programs, with nursing and physical therapy being the most common additional programs. Most library-led instruction occurred during the didactic phase and focused on search skills and evidencebased practice. PubMed and UpToDate were the most library-promoted resources. Two thematic elements discovered through the semi-structured interviews were "relationship building as paramount" and "impact of the learning curve on librarian workload." Conclusion: Librarians who support PA educational programs face challenges related to relationship building, financial resources, workload, and steep learning curves. The findings underscore the need for targeted professional development programs to equip librarians with the necessary knowledge and skills.